2011
DOI: 10.1029/2010ja015865
|View full text |Cite
|
Sign up to set email alerts
|

Flux transport, dipolarization, and current sheet evolution during a double-onset substorm

Abstract: [1] We study a substorm with two onsets (at 0220 and 0243 UT) that occurred during a gradual northward interplanetary magnetic field (IMF) turning on 16 February 2008. At these times, Time History of Events and Macroscale Interactions during Substorms (THEMIS) and GOES spacecraft were distributed between 6.6 and 18 R E downtail. Prior to the weak auroral electrojet onset at 0220 UT, a thin current sheet was extended near 10-11 R E . After the onset, Earthward fast flows with dipolarization fronts followed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 66 publications
2
42
1
Order By: Relevance
“…Alternately, the tearing instability may be initiated by the negative ∂ B Z /∂ X [ Sitnov and Schindler , 2010]. The possibility of normal reconnection after some reconnection‐preconditioning process was considered, by, e.g., Nakamura et al [2011]. They suggested that a preceding reconnection took the magnetic flux away and created a second diffusion region, provoking another reconnection.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Alternately, the tearing instability may be initiated by the negative ∂ B Z /∂ X [ Sitnov and Schindler , 2010]. The possibility of normal reconnection after some reconnection‐preconditioning process was considered, by, e.g., Nakamura et al [2011]. They suggested that a preceding reconnection took the magnetic flux away and created a second diffusion region, provoking another reconnection.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Such structure, widely believed as a consequence of magnetic reconnection (Birn et al, ; Fu, Khotyaintsev, et al, ), can propagate both earthward and tailward (Angelopoulos et al, ; Fu, Cao, et al, ; Ohtani et al, ). The earthward BBF transports a large amount of mass and magnetic fluxes toward the Earth and subsequently triggers the substorm activity (e.g., Angelopoulos et al, ; Cao et al, ; Ergun et al, ; Fu et al, ; J. Liu et al, ; Ma et al, ; Nakamura et al, ; Panov et al, ; Sergeev et al, ; Xu, Fu, Norgren, et al, ; Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The dipolarization front (DF) is frequently observed [ Nakamura et al , 2002; Runov et al , 2009; Fu et al , 2011a; Schmid et al , 2011] in the Earth's magnetotail associated with the bursty bulk flow (BBF) [ Angelopoulos et al , 1992]. It receives much attention recently due to its important role in the flux transport event [e.g., Volwerk et al , 2008; Nakamura et al , 2009, 2011; Birn et al , 2011]. Both simulations [e.g., Sitnov et al , 2009; Sitnov and Swisdak , 2011; Birn et al , 2011; Wu and Shay , 2012] and observations [e.g., Runov et al , 2012] suggested that the DF can be produced by magnetic reconnection.…”
Section: Introductionmentioning
confidence: 99%